The effect of biofuel addition to flight kerosene on a rubber gasket - Olšovský, Milan; Hocko, Marián (Transport, 2011)
This paper solves a problem of using unconventional fuels for driving jet engines. The carried out experiments were aimed at assessing the possibilities of using various contributions of MERO (methyl esters of rapseed oil) biofuel mixed with Jet A-1 aircraft fuel and for analyzing the influences of using an alternative fuel exerted upon the selected parts of the jet engine. The authors of the article compare the effect of adding bio-ingredients (MERO) to Jet A-1 aircraft fuel on the properties of rubber sealings used in the aircraft engine. The physical properties of MERO bio-ingredients and Jet A-1 aircraft fuel are very similar. The conducted research has discovered additional options of mixing MERO biofuel and Jet A-1 aircraft fuel and demonstrated that the total concentration (0–100%) of MERO biofuel in Jet A-1 aircraft fuel reaches a process of creating of a homogeneous mixture without sediments or coagulants. The evaluated results indicate that the appendage of the methyl esters of rapseed oil in Jet A-1 aircraft fuel give out a relatively large slump in physical-mechanical properties within the period of a few days. The raising content of MERO in aircraft fuel is bulking samples and makes itself felt by increasing the weight of the samples.First Published Online: 12 Apr 2011